FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM DETEKSI DINI KANKER SERVIKS MELALUI PEMERIKSAAN IVA (INSPEKSI VISUAL ASAM ASETAT) DI PUSKESMAS WILAYAH KOTA SURABAYA - Anggraini, Fritria Dwi (Unusa Press, 2014)
Cervical cancer detection program through an examination of the IVA has been implemented in all health centers in Surabaya since 2010. Target of this program are 80 % WUS and the target examination at least 25 people per month , but the achievement only 3-4 people permonth. The purpose of research is to analyze the factors that affect the implementation of IVA’s programs in healthcare centers in  Surabaya .Research conducted observational analytic cross sectional approach . The study population was responsible for IVA program at the health center for 52 people with a total sampling . The data was collected through interviews with  questionnaire . Analyzed using T test track with the program VPLS. The results showed IVA program by parent centers in the city of Surabaya 57.7 % poor , 51.9 % of communication is not good , the attitude of the respondents 55.8 % positive / supportive IVA program, character health centers provide less at 53.8 % support , understanding of the standard and target 51.9 % less understand . Based on the test results showed that the communication model of the structure , characteristics and health centers responsible attitude directly affects the implementation of the  program , while managing and understanding of the standard target indirectly influence the IVA program implementation through communication and attitud. Taken together these five factors influence the implementation of the IVA program with a contribution of 82.7 % which is the most influential variable is communication.